Mixing of mineral dust with urban pollution aerosol over Dakar (Senegal): Impact on dust physico-chemical and radiative properties. - Petzold, A.; Veira, A.; Mund, S.; Esselborn, M.; Kiemle, C.; Weinzierl, B.; Hamburger, T.; Ehret, G.; Lieke, K.; Kandler, K. (Tellus B: Chemical and Physical Meteorology, 2011)
In the framework of the Saharan Mineral Dust Experiment (SAMUM) in 2008, the mixing of the urban pollution plume of Dakar (Senegal) with mineral dust was studied in detail using the German research aircraft Falcon which was equipped with a nadir-looking high spectral resolution lidar (HSRL) and extensive aerosol in situ instrumentation. The mineral dust layer as well as the urban pollution plume were probed remotely by the HSRL and in situ. Back trajectory analyses were used to attribute aerosol samples to source regions.We found that the emission from the region of Dakar increased the aerosol optical depth (532 nm) from approximately 0.30 over sea and over land east of Dakar to 0.35 in the city outflow. In the urban area, local black carbon (BC) emissions, or soot respectively, contributed more than 75% to aerosol absorption at 530 nm. In the dust layer, the single-scattering albedo at 530 nm was 0.96 Ã¢ÂÂ 0.99, whereas we found a value of 0.908 ÃÂ± 0.018 for the aerosol dominated by urban pollution. After 6h of transport over the North Atlantic, the externally mixed mode of secondary aerosol particles had almost completely vanished, whereas the BC agglomerates (soot) were still externally mixed with mineral dust particles.